Acute exercise mobilizes CD8+ cytotoxic T cells and NK cells in lymphoma patients - Koivula, Tiia; Lempiäinen, Salla; Rinne, Petteri; Hollmén, Maija; Sundberg, Carl Johan; Rundqvist, Helene; Minn, Heikki; Heinonen, Ilkka (Frontiers in Physiology, 2023)
Background: Studies have shown that acute exercise can mobilize several leukocyte subpopulations in healthy individuals. Our aim was to investigate whether a 10-min acute exercise has an effect on immune cell proportions in lymphoma patients. Methods: This study included seven lymphoma patients referred to curative oncologic therapy. Three had Hodgkin and four non-Hodgkin lymphoma, one was female, and their mean age was 51. Patients underwent a 10-min acute exercise on a bicycle ergometer at moderate exercise intensity. Whole blood samples were taken at rest, immediately after exercise, and 30 min after exercise. Leukocyte subpopulation levels were determined using flow cytometry. Results: Proportions of total NK cells and CD56+CD16+ NK cells of total leukocytes increased immediately after exercise and decreased back to baseline at 30 min post-exercise. Proportion of CD8+ T cells of total T cells increased and proportion of CD4+ T cells of total T cells decreased immediately after exercise, and both returned to baseline at 30 min post-exercise. There was no change in the proportions of B cells, granulocytes, or monocytes. Exercising diastolic blood pressure correlated positively with changes in total NK cell and CD56+CD16+ NK cell proportions, and exercising mean arterial pressure correlated positively with change in CD56+CD16+ NK cell proportion. Conclusion: Our findings indicate that a single acute exercise bout of only 10 min can cause leukocytosis in lymphoma patients, particularly on cytotoxic T cells and NK cells, which are the most important immune cells fighting against cancer.